Pedestrian Friendly Environment in Residential Complexes Case Study Erbil - Sana Sati Abbas; Asmaa Omar Al.Talib (Iraqi Journal of Architecture and Planning, 2018)
This paper studies the concept of Pedestrian Friendly Environment in Residential complexes. It's defined it as (an environment that posses number of design and social characteristics, such as safety, vitality, connected and accessible. Also interesting, comfortable, through good design of pedestrian axes, mixed use and sustainable transportation. The research problem is that (there is a knowledge gap about the characteristics of this environment, and its treatment in residential complexes locally .The research hypothesis is that (The Pedestrian Friendly Environment in Residential complexes materialized through, planning dimensions, design and environmental characteristics and treatments). The paper found that the aim of pedestrian friendly environment is to improve the body activities, increase the quality of space and the social interaction, materialized the sustainable transportation. The planning dimensions were the intense mixed use, and the design of pedestrian axes. The main design characteristics were accessibility, vitality, permeability and safety. And finally providing   shads as environmental treatment.